Net Generation Student Teachers: How Tech-Savvy Are They? - Narasuman, Suthagar; Md. Yunus , Md. Rizal; Ahmad Kamal, Azlan (Penerbit Universiti Sains Malaysia, 2011)
The present generation of young people is often touted as tech-savvy. They have been variously termed as the "Y Generation" and the "Net Generation" to reﬂect their technologically inclined nature and living environment. The thrust of this study is to assess student teachers' attitudes, knowledge of ICT (Information Communication Technology) and their context of ICT usage. These factors are important in assessing the tech worth or ICT profciency of this generation of student teachers in higher education. Information-seeking is a behaviour that is tempered by culture and education within the paradigms of a complex social context and not an intuitive behaviour as posited by the Net Generation Theorists. The fndings of this study point to a generation that is undoubtedly active in engaging with technology but not for the reasons cited by Net Generation Theorists. This study utilised a survey method, and data were collected through a self-reported survey questionnaire. Group interviews were conducted to further validate the data obtained. The respondents for this study are student teachers undertaking a bachelor's degree in education at a tertiary institution in Malaysia.